Sleep Disturbances Increase the Impact of Working Memory Deficits on Learning Problems in Adolescents with High-Functioning Autism Spectrum Disorder. - Calhoun, Susan L.; Pearl, Amanda M.; Fernandez-Mendoza, Julio; Durica, Krina C.; Mayes, Susan D.; Murray, Michael J. (Journal of Autism & Developmental Disorders, 2020)
Sleep disturbances (SD) are prevalent in individuals diagnosed with Autism Spectrum Disorder (ASD). Less is known about the effects of SD on cognition and learning in adolescents with high-functioning ASD (HF-ASD). Adolescents with HF-ASD (N = 96) were evaluated for the relationships of SD to working memory and learning problems. Results found SD to modify the relationship between working memory and learning problems. Working memory deficits were associated with learning problems among those with SD, while not among those without SD. SD and working memory deficits should be targeted in interventions for these adolescents with HF-ASD (e.g., cognitive behavior therapy for insomnia, pharmacological treatments). Future studies should examine if improvement in SD reduces the impact of working memory deficits on learning problems.